Bouncing Back to the Future: A Look at the Road Ahead for the Assessment of Resilience. Issue 2 (4th July 2016) - Harms, P. D.; Wood, Dustin
Abstract : We appreciate the authors of the target article (Britt, Shen, Sinclair, Grossman, & Klieger, 2016 ) shining a spotlight on the important work being done in the study of resilience and providing a historical overview of how resilience has been conceptualized and assessed in the past. To add to this review, we would briefly like to comment on current developments in the field of resilience and related fields that may have broader implications for both the study of resilience and for many other topics in the industrial–organizational literature as well.